Efektivitas Model Pembelajaran Problem Based Learning Dengan Media “Vlab Suhu Dan Kalor” Terhadap Hasil Belajar - Aulia, Rini Shoffa; Chusni, Muhammad Minan; Kariadinata, Rahayu (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model using the “Vlab Suhu dan Kalor” media on students’ learning outcomes. This research employed a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 33 seventh-grade students who were given tests before and after the treatment. Data analysis was conducted through a normality test, hypothesis test, and N-Gain calculation. The results of the normality test showed that the data were normally distributed, while the hypothesis test obtained a significance value of < 0.05, indicating a significant difference between the pretest and posttest learning outcomes. The average N-Gain score of 62.97% falls into the medium category, showing a fairly effective improvement in learning outcomes. It can be concluded that the application of the PBL model using the “Vlab Suhu dan Kalor” media effectively enhances students’ science learning outcomes on the topic of heat and temperature.